Perbandingan Strategi Group Investigation Dengan Examples Non Examples Terhadap Hasil Belajar Ipa Kelas IV SDN Manahan Tahun 2015/2016 - Saputri, Emalia; , Drs. Mulyadi SK,SH.,M.Pd (2016)
The purposeof this studyisto : (1) Know the differencebetween theeffect ofusing strategy Group Investigation with Examples non Examples strategy on learning outcomesfourthgrade science studentsSDN Manahanthe academic year2015/2016. (2) know the effect ofa larger strategybetween strategywith the strategyGroup Investigation Examples non Examplesto the learning outcomesof studentsIVSDN Manahanthe academic year2015/2016Subjects in this study were class IV SDN Manahan , which consists of class IVA totaling 33 students who applied strategy Group Investigation and IVB totaling 321 students who applied strategies Examples non Examples .Data collection methodsused aretests anddocumentation. Data analysis techniqueused isthe t test, whichpreviouslyperformedthe prerequisite testanalysis is thebalance testwithF test, test for normalitywith theKolmogorov-Smirnov method.. Fromthe data analysiswith a significance levelof 5%can be concludedthat: (1) There is adifference of influencestrategieswithstrategiesGroup Investigation Examples non Examples on learning outcomesfourthgrade science studentsSDN Manahan the academic year2015/2016. Based on t testobtained t count>t table is-1,301>2,000 sothe hypothesisThere is a differencebetween theeffects ofthe strategywith theGroup Investigation Examples non Exampleson the results offourth-grade studentslearn scienceSDN Manahanacceptableacademic year2015/2016. (2) Strategy Group Investigationgreater influencethanstrategyExamples non Exampleson learning outcomesfourthgrade science studentsSDN Manahanthe academic year2015/2016.The average value of learning outcomes IPA IVA class by using strategy and IVB Group Investigation using the strategy Examples non examples , ie 69,54<72,65so the hypothesis Strategy Group Investigation effect is greater than the strategy Examples non Examples on learning outcomes IPA class IV SDN Manahan acceptable academic year 2015/2016.